Toxicological evaluation of Cladophora glomerata Kützing and Microspora floccosa Thuret in albino rats. - Prannapus Fahprathanchai (2018)
This study aimed to evaluate the toxicity of Cladophora glomerata and Microspora floccosa ethanolic extracts in rats. Acute toxicity was tested with a single oral administration of the extract at a dose of 25 g/kg bd wt. Mortality, behavior, amount of food intake, body weight, and any abnormalities of the visceral organs, were observed. The results showed that the extract caused neither mortality, nor abnormalities. Subchronic toxicity was tested by administering the extract at doses of 0.5 g/kg and 1.0 g/kg for 60 days. Differences in body weight, hematology and blood biochemistry (alanine aminotransferase, ALT; aspartate aminotransferase, AST; blood urea nitrogen, BUN and creatinine, Cre) were not detected among the control and treatment groups. Although the packed cell volume of the male rats treated with 1.0 g/kg extract was significantly lower than the controls (p< or =0.05), the level was in the standard range for rat hematocrit.